INTERNATIONAL STUDENTS GET-TOGETHER TO SHARE IDEAS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 24 September 2016 – The Post Graduate Office, School of Medical Sciences (PPSP), Universiti Sains Malaysia (USM) recently organised an International Students’ GetTogether Day, which provided an informal setting for the international students to share ideas, experiences and challenges during their studies in USM.